Genre in World Englishes Case Studies from the Caribbean. - Muehleisen, Susanne (Varieties of English around the world ;, 2022)
World Englishes and English in postcolonial contexts have been curiously neglected in an otherwise abundant research literature on text types and genres in English. This volume looks at the adaptation, transformation and emergence of genres in the particular cultural context of the Anglophone Caribbean.